Primary motor cortex inhibition in spinal cord injuries - Kříž, Jiří; Kozak, Jiří; Zedka, Milan (Neuro-endocrinology letters, 2012)
OBJECTIVES AND METHODS: Excitability changes in the primary motor cortex in 17 spinal-cord injured (SCI) patients and 10 controls were studied with paired-pulse transcranial magnetic stimulation. The paired pulses were applied at inter-stimulus intervals (ISI) of 2 ms and 15 ms while motor evoked potentials (MEP) were recorded in the biceps brachii (Bic), the abductor pollicis brevis (APB) and the tibialis anterior (TA) muscles. RESULTS: The study revealed a significant decrease in cortical motor excitability in the first weeks after SCI concerning the representation of both the affected muscles innervated from spinal segments below the lesion, and the spared muscles rostral to the lesion. In the patients with motor-incomplete injury, but not in those with motor-complete injury, the initial cortical inhibition of affected muscles was temporarily reduced 2-3 months following injury. The degree of inhibition in cortical areas representing the spared muscles was observed to be smaller in patients with no voluntary TA activity compared to patients with some activity remaining in the TA. Surprisingly, motor-cortical inhibition was observed not only at ISI 2 ms but also at ISI 15 ms. The inhibition persisted in patients who returned for a follow-up measurement 2-3 years later. CONCLUSION: The present data showed different evaluation of cortical excitability between patients with complete and incomplete spinal cord lesion. Our results provide more insight into the pathophysiology of SCI and contribute to the ongoing discussion about the recovery process and therapy of SCI patients.
Keywords: Analysis of Variance; dospělí; kosterní svaly; neurony eferentní; Female; Neurons, Efferent; nervový útlum; Adult; mladý dospělý; ženské pohlaví; Adolescent; Time Factors; časové faktory; Neural Inhibition; lidé; transkraniální magnetická stimulace; Motor Cortex; poranění míchy; studie případů a kontrol; Muscle, Skeletal; referenční hodnoty; motorické evokované potenciály; Spinal Cord Injuries; Evoked Potentials, Motor; analýza rozptylu; Male; Case-Control Studies; motorické korové centrum; Reference Values; Young Adult; eferentní nervové dráhy; Efferent Pathways; Transcranial Magnetic Stimulation; lidé středního věku; mužské pohlaví; Middle Aged; mladiství; Humans